Is an Identity Crisis Possible in “Erdogan-ized” Turkey? - Ralchev, Plamen (Research Papers, 2018)
The aim of this paper is to analyze the results of the referendum in Turkey in 2017, which revealed a deep polarization of Turkish society. The argument builds on the hypothesis of an identity crisis and risk of increasing protest movements of secular circles in Turkey. The paper critically reviews the religious conservatism in the country as being imposed through schools, as well as through universities – the institutions that are bound to form the mindset and views of the young generations in Turkey.
Keywords: Turkey; Referendum 2017; Societal split; Identity crisis